The protective effect of pomegranate extract against cisplatin toxicity in rat liver and kidney tissue. (8th August 2015) - Bakır, Salih; Yazgan, Ümit Can; İbiloğlu, İbrahim; Elbey, Bilal; Kızıl, Murat; Kelle, Mustafa
Abstract: Objectives : The purpose of this study was to perform a histopathological investigation, at the light microscopy level, of the protective effects of pomegranate extract in cisplatin-induced liver and kidney damage in rats. Material and methods : Twenty-eight adult male Wistar albino rats were randomly divided into four groups of seven animals: Group 1: Control; Group 2: Treated for 10 consecutive days by gavage with pomegranate juice (2 ml/kg/day); Group 3: Injected intraperitoneally with cisplatin (8 mg/kg body weight, single dose) onset of the day 5, and Group 4: Treated by gavage with pomegranate juice 10 days before and after a single injection of cisplatin onset of the day 5. After 10 days, the animals were sacrificed and their kidneys and liver tissue samples were removed from each animal after experimental procedures. Cisplatin-induced renal and hepatic toxicity and the effect of pomegranate juice were evaluated by histopatological examinations. Results : In the kidney tissue, pomegranate juice significantly ameliorated cisplatin-induced structural alterations when compared with the cisplatin alone group. But in the liver tissue, although pomegranate juice attenuated the cisplatin-induced toxicity only in two rats, significant improvement was not observed. Conclusion : In conclusion, these results demonstrate that the anti-oxidant pomegranate juice might have a protective effect against cisplatin-induced toxicity in rat kidney, but not in liver. Pomegranate juice could be beneficial as a dietary supplement in patients receiving chemotherapy medications.